Currency Bloc Formation as a Dynamic Process Based on Trade Network Externalities - Yehoue, Etienne (Washington, D.C. : International Monetary Fund, 2004)
The recent experience of the European Economic and Monetary Union (EMU) has stimulated the debate over currency union and reinforced the incentive for the emergence of currency blocs in other regions of the world. This paper builds a dynamic stochastic model-based on network externalities operating through trade channels-to explain the emergence of currency blocs, and specifically, why some countries join a currency union earlier than others. The paper develops and formalizes the intuition that currency bloc formation is path dependent, and that countries join currency blocs sooner the more they trade with the bloc member countries, with each additional member serving in a dynamic way to attract more members into the bloc. Evidence from the current pattern of EMU expansion supports the model, which is later used to elaborate on the pattern of further expansion of the union.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet